Tuberculosis Drug Discovery: Challenges and New Horizons - Fernandes, Guilherme F. S.; Thompson, Andrew M.; Castagnolo, Daniele; Denny, William A.; Santos, Jean L. dos [UNESP] (American Chemical Society (ACS), 2022)
Over the past 2000 years, tuberculosis (TB) has claimed more lives than any other infectious disease. In 2020 alone, TB was responsible for 1.5 million deaths worldwide, comparable to the 1.8 million deaths caused by COVID-19. The World Health Organization has stated that new TB drugs must be developed to end this pandemic. After decades of neglect in this field, a renaissance era of TB drug discovery has arrived, in which many novel candidates have entered clinical trials. However, while hundreds of molecules are reported annually as promising anti-TB agents, very few successfully progress to clinical development. In this Perspective, we critically review those anti-TB compounds published in the last 6 years that demonstrate good in vivo efficacy against Mycobacterium tuberculosis. Additionally, we highlight the main challenges and strategies for developing new TB drugs and the current global pipeline of drug candidates in clinical studies to foment fresh research perspectives.